2021
DOI: 10.1093/rheumatology/keaa915
|View full text |Cite
|
Sign up to set email alerts
|

Imbalanced MMP-3 and MMP-12 serum levels in systemic lupus erythematosus patients with Jaccoud’s arthropathy and a distinctive MRI pattern

Abstract: Objective Metalloproteinase (MMP)-3 and MMP-12 are proteolytic enzymes especially implicated in joint inflammation. This study aims to evaluate their association with arthritis features and hand MRI abnormalities in patients with SLE. Methods Fifty SLE patients, with a mean (s.d.) age of 48.1 (14.6) years were tested for MMP-3 and MMP-12 serum levels, then further classified according to the presence of X-ray erosions and joi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 30 publications
0
6
0
1
Order By: Relevance
“…82 Finally, Piga and colleagues observed higher levels of MMP3 in SLE patients with JA in comparison with those without this deforming arthropathy; conversely, lower levels of MMP12 were observed in the same group of patients. 83…”
Section: Biomarkers In Systemic Lupus Erythematosus-related Arthritismentioning
confidence: 99%
“…82 Finally, Piga and colleagues observed higher levels of MMP3 in SLE patients with JA in comparison with those without this deforming arthropathy; conversely, lower levels of MMP12 were observed in the same group of patients. 83…”
Section: Biomarkers In Systemic Lupus Erythematosus-related Arthritismentioning
confidence: 99%
“…Since erosive JA also shows characteristics of RA, we proposed that patients with SLE and erosive JA should be regarded as having rhupus. Contrary to the traditional view, some literatures have reported that JA patients without radiography findings can be detected fewer and smaller bone erosion than rhupus patients through ultrasound, CT and MRI 35,36 . Therefore, the severity of bone erosion may be the real key to distinguish the two diseases.…”
Section: Discussionmentioning
confidence: 92%
“…Contrary to the traditional view, some literatures have reported that JA patients without radiography findings can be detected fewer and smaller bone erosion than rhupus patients through ultrasound, CT and MRI. 35 , 36 Therefore, the severity of bone erosion may be the real key to distinguish the two diseases. However, it is not excluded that these SLE patients may actually have rhupus.…”
Section: Discussionmentioning
confidence: 99%
“…Cytokines are strongly related to tissue repair and destruction mechanisms, modulating the extracellular matrix (ECM) homeostasis by promoting the production of metalloproteinases (MMPs) and other enzymes. Recently, the serum levels of higher MMP-3 and lower MMP-12 were associated with JA deformities, and most importantly, their levels were associated with capsular swelling and oedematous tenosynovitis, the most prevalent hand MR changes in patients with JA [ 32 ]. This evidence suggests that both inflammation and impaired mechanisms of tissue remodeling might be involved in the development of JA.…”
Section: Pathogenesis Of Sle: Focus On the Musculoskeletal Manifestat...mentioning
confidence: 99%
“…Among these, the possible role of MMP-3 and MMP-12 serum levels has been investigated, with regard to their ability to discriminate different phenotypes of SLE-related joint involvement. In particular, MMP-3 serum levels were significantly higher in JA patients compared with rhupus syndrome and NDNE arthritis [ 32 ]. Finally, the possibility to search biomarkers in other anatomical sites involved in erosive arthritis development from a pathogenic point of view is very attractive.…”
Section: Pathogenesis Of Sle: Focus On the Musculoskeletal Manifestat...mentioning
confidence: 99%